Metastatic Prostate Mass to the Intradural Foramen Magnum Region: A Case Report - Quillin, Joseph; Chittiboina, Prashant; Haydel, Justin; Nanda, Anil (Journal of Neurological Surgery Reports, 2012)
Intradural metastatic tumors of the foramen magnum region are extremely rare tumors. We report a 73-year-old patient that presented with right hemiparesis and a recent history of prostate biopsy for an enlarged prostate. Imaging revealed an anterolateral intradural foramen magnum mass with compression of the medulla. A right far lateral approach with condyle preservation was used to resect the mass. Pathological examination revealed the tumor as a metastatic prostate mass. The patient had a significant recovery of motor function and was given adjuvant external beam radiation. At the time of last follow-up, the patient had good clinical relief from the preoperative symptoms. To our knowledge, this is the first reported case of an intradural foramen magnum prostate tumor metastasis. We report on multimodal management of this rare, yet morbid presentation of a common tumor.
Keywords: foramen magnum; prostate; metastatic tumor; intradural; far lateral